Historical Trajectory of the Development of the Concept of Civil Society in Europe: From Aristotle to Gramsci - Tanvir Anjum (Journal of Political Studies, 2010)
The term civil society has become a part of the contemporary political lexicon. Despite its popularity in the contemporary development discourse, it is a polysemous concept, which has been given different meanings in varied historicaltemporal contexts in Europe by thinkers and theorists having diverse theoretical positions. That is why the concept is characterized by much theoretical ambiguity and conceptual complexity. The present article intends to explore the development of the concept of civil society in Europe through the ages in a historical perspective since it is a historicallyembedded concept. Civil society was understood as a political community by Aristotle, as a sphere of absolute sovereignty or state in contrast to the state of nature by Hobbes and Locke, as a critique to absolutism or monarchy by Montesquieu and Kant, as a self-regulatory and selfgoverning society in opposition the state by Ferguson, as a realm of economic relations by Smith, as a legal sphere of the state by Hegel, as an economic structure in a polity by Marx, as a realm of secondary institutions and intermediary organizations by de Tocqueville, and as a domain of voluntary associations counterpoint to the state by Gramsci. This paper is an attempt to briefly investigate and examine the contributions of the above-mentioned political thinkers and theorists in the conceptual development of the idea of civil society.